Early Neurodevelopmental Anomalies in Young Rats from Adult female Treated with Valproic Acid - Martial Miguel, Landry; Emmanuel Mboungou Malonga, Archange; Gesril Njilo Tchatchouang, Didier; LÃ©kana, ChildÃ©rick; Ravelle Dobhat-Doukakini, Choupette; Grace Nkounkou Matondo, Emmanuel; Bertrand Bolanga, Ruphin; Moukassa, Donatien; Antoine Abena, Ange (International Journal of Pharmacology and Toxicology, 2021)
Background: the influence of VPA on murine fertility, and on offspring is well documented: VPA decreases the fertility rate (by 25%) and the number of fÅ“tus. Furthermore, VPA causes behavioral alterations in rodents similar to the symptoms observed in autism.Objective: in this study we investigated the effects of exposure of non-pregnant adult rats to VPA in the offspring of these animals.Material and methods: non-pregnant adult rats were divided into 3 groups; (1) distilled water group, (2) VPA 200 mg / kg group and (3) VPA 400 mg/kg group. The products were administered orally daily for 30 days. At the end of treatments, all rats were put into monogamous mating with breeding males. The zootechnical characteristics (gestation period, litter size, mortality rate) were then noted. The young rats were then subjected to a battery of behavioral tests (reversal and anti-gravity reflexes, cliff avoidance, suspension, motor coordination and eye opening), carried out at different stages of life to assess sensorimotor development. Morphological abnormalities were also sought, as well as the mortality rate on the 28th day of life.Results: An increase in the mortality rate and a decrease in the mean lifespan were found in female rats exposed to VPA. Young rats from female rats exposed to VPA showed decreased success rates and performance in behavioral testing. Morphodevelopmental abnormalities such as adictalia or stump necrosis were found in the VPA groups. The offspring mortality rate of female rats exposed to VPA 200 mg/kg was 100%.Conclusion: VPA administered to non-pregnant adult rats causes developmental abnormalities, decreased success rates for performance testing, deformities and increased mortality in young rats from the treated rats by VPA.Â Â